1978
DOI: 10.1037/0021-9010.63.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monetary rebates, feedback, and information on residential electricity conservation.

Abstract: In this study, conducted during the summer months in Texas, 129 volunteer participant households were assigned to one of five experimental conditions: a high monetary rebate condition in which participants received conservation information, weekly written feedback on their electricity use, and monetary rebates amounting to a 240% price change in electricity; a low monetary rebate condition with the same structure as the high rebates except payments amounted to a 50% price change; a weekly feedback condition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…An obvious method to achieve energy conservation is to provide economic incentives to reduce energy consumption (Winett et al, 1978;Midden et al, 1983;Petersen et al, 2007;Mizobuchi and Takeuchi, 2012). A number of empirical studies have estimated how detailed information on power use can contribute to energy conservation (Sexton et al, 1989;Wood and Newborough, 2003;Delmas et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An obvious method to achieve energy conservation is to provide economic incentives to reduce energy consumption (Winett et al, 1978;Midden et al, 1983;Petersen et al, 2007;Mizobuchi and Takeuchi, 2012). A number of empirical studies have estimated how detailed information on power use can contribute to energy conservation (Sexton et al, 1989;Wood and Newborough, 2003;Delmas et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have demonstrated that regular feedback on energy use can reduce consumption (Becker, 1978;Hayes & Cone, 1977;Kohlenberg, Phillips, & Proctor, 1976;Palmer, Lloyd, & Lloyd, 1978;Seligman & Darley, 1977;Winett, Kaiser, & Haberkorn, 1977;Winett, Neale, & Grier, 1979). Monetary rebates based on decreases in energy consumption have also been shown to be effective means of reducing residential energy use (Winett, Kagel, Battalio, & Winkler, 1978;Winett & Nietzel, 1975 There is a category of residential units in which there is someone with a strong interest in getting residents to conserve energy. These are master-metered apartments, in which residents do not pay for their own energy use directly.…”
mentioning
confidence: 99%
“…These results are in line with some previous studies. That is to say, some field studies have indicated that economic rewards (e.g., money or prizes) have been successful in reducing household energy consumption (Winett et al, 1978;Midden et al, 1983;McClelland & Cook, 1980;Petersen et al, 2007). Moreover, social comparisons can be an effective strategy in motivating people to save energy because it facilitates social learning about the individuals' optimal level of energy use (Cai et al, 2009;Munshi & Myaux, 2006).…”
Section: Resultsmentioning
confidence: 99%